Unusual cause of chest pain: empyema necessitans and tubercular osteomyelitis of the rib in an immunocompetent man. (4th January 2016) - Dunphy, Louise; Shetty, Prashanth; Kavidasan, Ajitkumar; Rice, Alexandra
Abstract : A 33-year-old man, born in India but resident in the UK for 5 years, presented to the emergency department with a 4-week history of a dry cough and right-sided pleuritic chest pain. He reported systemic features, including fever and unintentional weight loss. His medical history included vitamin D deficiency. He had travelled to India 10 months previously and denied any exposure to tuberculosis (TB). He was an ex-smoker with a 20 pack history. Respiratory examination confirmed decreased air entry of the right lower lobe and stony dullness on percussion. His C reactive protein was 178 mg/L. A chest radiograph identified a moderate-sized right-sided pleural effusion and destruction of the lateral aspect of the right fifth rib, strongly suggestive of underlying malignancy. Further investigation with a CT of the thorax identified a focal lytic lesion in the right fifth rib, at its lateral aspect, with expansion of the rib observed. Ultrasound-guided pleural aspiration confirmed an exudative pleural effusion. Gram stain revealed no organisms or polymorphs. Four days post admission, the patient was transferred to the regional thoracic surgery unit and underwent video-assisted thoracic surgery, bronchoscopy and drainage of his empyema. His Mantoux tuberculin skin test and his TB Elispot were negative, suggesting that TB infection was unlikely. Culture confirmed no growth after 48 h incubation. Histology of his pleural biopsy identified multiple non-confluent necrotising granulomatous inflammation with very occasional acid–alcohol-fast bacilli-like organisms, highly suspicious for mycobacterial infection. The isolate, Mycobacterium tuberculosis, was identified by Accuprobe and HAIN tests, respectively. MPT64 erythrocyte sedimentation rate (ESR) results from the fifth rib were positive for M. tuberculosis . This case report discusses the aetiology, clinical presentation and pathophysiology of both empyema necessitans and tubercular osteomyelitis of the rib.